E-Servqual Tokopedia And E-Customer Loyalty In Indonesia - R. Yogie Prawira (SEAN Institute, 2024)
This study investigates the effect of the e-SERVQUAL dimension in e-commerce on e-customer loyalty. With a quantitative approach, data were collected from 97 Tokopedia e-commerce users using a structured questionnaire, and the theoretical model was tested using multiple linear regression analysis. The results found that Tokopedia's e-SERVQUAL variable which includes Efficiency, Personal Need, Reliability, Responsiveness, Site Organization, User Friendliness as a whole has an effect on e-customer loyalty. However, partially, not all variables have a direct effect on Tokopedia's e-customer loyalty, namely the Efficiency, Responsiveness, and Site Organization variables. The other variables that have a direct effect are Personal Need, Reliability, and User Friendliness.